Abrogating the interplay between IGF2BP1, 2 and 3 and IGF1R by let-7i arrests hepatocellular carcinoma growth. (2nd January 2016) - Fawzy, Injie Omar; Hamza, Mohammed Tarif; Hosny, Karim Adel; Esmat, Gamal; Abdelaziz, Ahmed Ihab
Abstract: IGF2BP 1, 2 and 3 control the fate of many transcripts. Immunoprecipitation studies demonstrated the IGF2BPs to bind to IGF1R mRNA, and our laboratory has recently shown them to post-transcriptionally regulate IGF1R. This study sought to identify a microRNA regulating the IGF2BPs and consequently IGF1R. All three IGF2BPs were among the top-ranked predicted targets of let-7i. Let-7i was downregulated in HCC tissues, and transfection of HuH-7 with let-7i inhibited malignant cell behaviors and decreased IGF2BPs transcripts. Direct binding of let-7i to IGF2BP2 and IGF2BP3 3′UTRs was confirmed, and the effect of let-7i caused a decrease in the IGF2BPs' target gene, the IGF1R. IGF1R mRNA was inversely correlated with let-7i in HCC tissues and was reduced upon let-7i transfection into HuH-7. Reporter assays validated IGF1R as a target of let-7i. Therefore, let-7i may control HCC tumorigenesis by regulating IGF1R directly and indirectly by interrupting the interplay between IGF1R and the IGF2BPs.